PERAN KOPERASI SYARIAH DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA(Studi Kasus Pada BMT KUBE Sejahtera 008) - Maya Astrining Dewi; Marini; Aan Zulyanto; Amir Mukadar (Universitas Muhammadiyah Bengkulu, 2025)
This thesis examines the role of BMT KUBE Sejahtera 008 Sharia Cooperative in improving the welfare of its members in Sri Kuncoro Village, Central Bengkulu. The growing demand for accessible and affordable capital, particularly among Micro, Small, and Medium Enterprises (MSMEs), motivates this research to explore BMT's contribution within the context of a Sharia-based people's economy. This qualitative study employs a socio-legal approach, gathering primary data through interviews with BMT administrators and members, alongside secondary data from relevant literature and documents. The aim of this study is to elucidate the role of BMT KUBE Sejahtera 008 in enhancing member welfare and to identify the factors that support or hinder this process. The research findings highlight the significant role of BMT KUBE Sejahtera 008 in enhancing the economic welfare of its members. Easy access to financing and profit-sharing systems has proven effective in increasing income, particularly for micro, small, and medium enterprises. Despite challenges such as limited public awareness of BMT and funding constraints, BMT KUBE Sejahtera 008 has successfully built trust and member satisfaction. Overall, this study concludes that BMT KUBE Sejahtera 008 plays a vital role in improving the economic welfare of members in Sri Kuncoro Village, Central Bengkulu, and contributes positively to the village’s economy